The evolution of precision agriculture and food safety: a bibliometric study - Jiahui Xu; Yuanpei Cui; Shuhan Zhang; Meiping Zhang (Frontiers in Sustainable Food Systems)
IntroductionFood safety issues pose a significant threat to humanity. Precision agriculture leverages advanced technologies for real-time monitoring and management, improving agricultural productivity and sustainability while safeguarding food security. Nonetheless, acquiring a thorough comprehension of this continually shifting panorama remains of vital significance.MethodsThis study conducts a comprehensive bibliometric review of precision agriculture and food safety, utilizing quantitative methods to identify past, current, and future evolution. It includes citation, co-authorship, co-citation, and co-words analyses.ResultsPublications emerged in 1994 and began to rise significantly since 2019. Citation analysis verified influencing works and journals, whereas co-authorship analysis identified how authors, institutions, and countries collaborate in this field. Co-citation analysis then classified past and current hotspots into four clusters: remote vegetation monitoring techniques, technological innovations and agricultural decision-making, precision agriculture and sustainable development, and deep learning in agriculture. After that, the co-occurrence of keywords revealed emerging trends, such as precision cultivation and yield prediction, smart agricultural technology and food management, precision information for climate change adaptation, and precision agriculture and food security.DiscussionThe findings provide insights for scholars, policymakers, researchers, practitioners, and industry stakeholders. They guide future research directions and address pressing challenges in agriculture and food safety.